Large-scale 3D printing by a team of mobile robots - Tay, Daniel Yi Wei (2019)
Scalability is a problem common to most existing 3D printing processes, where the size of the design is strictly constrained by the chamber volume of the 3D printer. This issue is more pronounced in the building and construction industry, where it is impractical to have printers that are larger than actual buildings. One workaround consists in printing smaller pieces, which can then be assembled on-site. This workaround generates however additional design and process complexities, as well as creates potential weaknesses at the assembly interfaces. In this paper, we propose a 3D printing system that employs multiple mobile robots printing concurrently a large, single-piece, structure. We present our system in detail, and report simulation and experimental results. To our knowledge, this is the first physical demonstration of large-scale, concurrent, 3D printing of a concrete structure by multiple mobile robots.